Collisional merging formation of a field-reversed configuration in the FAT-CM device. (11th April 2019) - Asai, T.; Takahashi, T.; Sekiguchi, J.; Kobayashi, D.; Okada, S.; Gota, H.; Roche, T.; Inomoto, M.; Dettrick, S.; Mok, Y.; Binderbauer, M.W.; Tajima, T.; et al.
Abstract: Collisional merging formation of field-reversed configurations (FRCs) at super Alfvénic velocity have been successfully initiated in the FAT-CM device at Nihon University. It is experimentally evidenced that the quiescent FRC profile is formed in a self-organizational manner after distructive disturbances by the super Alfvénic collision of two translated magnetized plasmoids. A drastic increase of the excluded flux compared to the field-reversed theta-pinch formation section has also been observed. This formation process has an important role in realizing an FRC based high-beta reactor core to capture high-energy beam ions, and it has been clearly observed by magnetic diagnostics of excluded flux and internal probe array. The experimental results are compared with two-dimensional magnetohydrodynamic (MHD) simulation results computed for the typical conditions of the FAT-CM experiments. Collisional merging of the two separately translated FRCs causes a conversion of the kinetic energy to mostly thermal ion energy, which contrasts with the spheromak merging dominated by magnetic energy in an MHD manner, resulting in an increase of the ion pressure and polodal flux that drastically expands the FRC volume.